BIAS GENDER DALAM PERKAWINAN BEDA WANGSA PADA MASYARAKAT HINDU DI BALI - I Putu Sudarma (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
Society structure is formed based on its socio-cultural in Balinese empire era. The structure consists of tri wangsa that is dominant and jaba wangsa is as subordinate position. Those conditions imply to endogamy marriage in which a social group must marry with their same group. If they get married to the other group, they will have custom sanction called asupundung and alangkahi karang hulu. In this era, those custom sanctions are abrogated based on the decree of Balinese regional representative council No.11, July 12, 1951. It occurs because the sanctions are abusive and less of humanistic values. It also causes some disorders including discrimination to women’s right. This study employs qualitative approach with literature study as data collection. This result shows gender bias from different wangsa.